Financial Inclusion, Aggregate Income, and Poverty: Districts/Cities in Indonesia - Fauzia, Syafna; Shanty Oktavilia (Universitas Negeri Semarang, 2025)
This study aims to empirically explore the condition of financial inclusion and relation between financial services sector development, real sector growth, and poverty alleviation. This study focuses on 334 Indonesian districts and cities in 2021. Financial inclusion measured by the penetration, availability, and utilization of banking services, which accumulate into a financial inclusion index. To examine the direct and indirect effects of financial inclusion on poverty through aggregate income, the Hayes Process Macro bootstrapping technique was used. In 2021 Central Jakarta has the highest level of financial inclusion in Indonesia, with an index of 0.8. The main form of financial inclusion is the availability of commercial bank offices and rural banks, while bank account ownership and the use of deposit and loan products in the formal financial services sector play a smaller role in the financial inclusion of Indonesian districts and cities in 2021. The findings indicate that financial inclusion has a positive and significant effect on aggregate income, a negative and significant effect on poverty, and aggregate income can mediate the relationship between financial inclusion and poverty.